A Phase III Randomized Study Comparing a Chemotherapy with Cisplatin and Etoposide to a Etoposide Regimen without Cisplatin for Patients with Extensive Small-Cell Lung Cancer - Berghmans, Thierry; Scherpereel, Arnaud; Meert, Anne-Pascale; Giner, Vicente; Lecomte, Jacques; Lafitte, Jean-Jacques; Leclercq, Nathalie; Paesmans, Marianne; Sculier, Jean-Paul, for the European Lung Cancer Working Party (ELCWP) (Frontiers in Oncology, 2017)
Abstract Introduction: In a literature meta-analysis, we showed survival benefits for regimens including cisplatin (HR 0.61; 95 % CI, 0.57–0.66) and for those including etoposide (HR 0.65; 0.61–0.69). That benefit was mainly observed when etoposide alone or in combination with cisplatin were included in the chemotherapy regimens. Our objective was to determine if chemotherapy with both drugs improves survival in comparison to a non-platinum regimen with etoposide. Methods: Extensive-SCLC patients were randomised between cisplatin-etoposide (CE) and ifosfamide-etoposide-epirubicin (IVE) between 2000 and 2013. Results: 176 and 170 eligible patients were respectively allocated to CE and IVE (315 deaths were required before analysis). Objective response rates were not significantly different: 60 % with CE and 59 % with IVE. No statistically significant difference in median survival and 1-year and 2-year was observed with rates of 9.6 months, 31 % and 5 % for CE and 10 months, 39 % and 9 % for IVE respectively. HR was 0.84 (95 % CI 0.68-1.05, p=0.16). Only two prognostic factors for survival were retained in multivariate analysis: sex with HR=0.69 (95% CI 0.49-0.97, p=0.03) and PS with HR=0.53 (95% CI 0.49-0.97, p<0.0001). After adjustment for these prognostic factors, HR for survival was 0.83 (95% CI 0.65-1.08, p=0.17). There was more thrombopenia in the CE regimen and more leucopenia with IVE. Conclusion: Combination of CE failed to improve survival in comparison to an etoposide-containing regimen without cisplatin. https://clinicaltrials.gov/ct2/show/NCT00658580?term=ELCWP+01994&rank=1 NCT00658580